2017
DOI: 10.1016/j.pnpbp.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the adaptive immune system to mood regulation: Mechanisms and pathways of neuroimmune interactions

Abstract: Clinical and basic studies of functional interactions between adaptive immunity, affective states, and brain function are reviewed, and the neural, humoral, and cellular routes of bidirectional communication between the brain and the adaptive immune system are evaluated. In clinical studies of depressed populations, lymphocytes—the principal cells of the adaptive immune system—exhibit altered T cell subtype ratios and CD4+ helper T cell polarization profiles. In basic studies using psychological stress to mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 167 publications
(217 reference statements)
2
46
0
1
Order By: Relevance
“…In our study, higher levels of depression symptoms were associated with higher viral loads, a finding consistent with other studies (Amanor-Boadu et al, 2016;Herkenham & Kigar, 2016). However, this association was only found in women, the group with a smaller sample size.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, higher levels of depression symptoms were associated with higher viral loads, a finding consistent with other studies (Amanor-Boadu et al, 2016;Herkenham & Kigar, 2016). However, this association was only found in women, the group with a smaller sample size.…”
Section: Discussionsupporting
confidence: 92%
“…Anxiety and especially depression have consistently been associated with poor antiretroviral treatment (ART) adherence (Safren et al, 2016;Smith Fawzi et al, 2016;Tao et al, 2016;Tatum & Houston, 2016), and are linked to poor virological control and lower CD4 T cell counts (Amanor-Boadu et al, 2016;Herkenham & Kigar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that T cells may provide important modulatory functions on cytokine production in response to psychological stress. In support of this possibility, several studies, including work from our laboratory, have shown a beneficial role for CD4 + T cells in stress responsiveness [22, 23], hippocampal dependent memory [24, 25] and emotional behavior [26]. Moreover, studies also document a detrimental role for differentiated Th17 CD4 + cells during stress exposure [27], and for CD8+ T cells in models of stress-induced vascular inflammation in hypertension [2830].…”
Section: Introductionmentioning
confidence: 97%
“…Lymphocytes, the cells of the adaptive immune system, are found in almost every tissue and organ, including the brain (Kipnis et al, 2012). Accumulating evidence shows that lymphocytes influence behaviour by mediating direct or indirect production of cytokines and growth factors in specific compartments of the brain (Filiano et al, 2017;Herkenham & Kigar, 2017). A role for lymphocytes, mainly mediated by T lymphocytes, has been shown in memory Brynskikh et al, 2008;Wolf et al, 2009;Radjavi et al, 2014), emotional behaviours (Beurel et al, 2013;Rattazzi et al, 2013;Clark et al, 2014a) and stress responsiveness Lewitus et al, 2008;Clark et al, 2014bClark et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%